2017
DOI: 10.1523/jneurosci.0935-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Trial-by-Trial Recoding of Task-Set Representations in the Frontoparietal Cortex Mediates Behavioral Flexibility

Abstract: Cognitive flexibility forms the core of the extraordinary ability of humans to adapt, but the precise neural mechanisms underlying our ability to nimbly shift between task sets remain poorly understood. Recent functional magnetic resonance imaging (fMRI) studies employing multivoxel pattern analysis (MVPA) have shown that a currently relevant task set can be decoded from activity patterns in the frontoparietal cortex, but whether these regions support the dynamic transformation of task sets from trial to trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
61
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 49 publications
9
61
3
Order By: Relevance
“…Consistent with the results of previous fMRI decoding studies (Etzel et al, 2016;Qiao, Zhang, Chen, & Egner, 2017;Woolgar et al, 2011;Waskom et al, 2014;Wisniewski et al, 2015), RSA successfully tracked neural representations for task rule information. In using this approach, our results replicate the fMRI findings of Etzel et al (2016) in human electroencephalographic data, showing that high reward prospect increased average task coding prior to target onset, and that the difference in task coding between reward conditions was associated with improvements in cognitive performance.…”
Section: Discussionsupporting
confidence: 86%
“…Consistent with the results of previous fMRI decoding studies (Etzel et al, 2016;Qiao, Zhang, Chen, & Egner, 2017;Woolgar et al, 2011;Waskom et al, 2014;Wisniewski et al, 2015), RSA successfully tracked neural representations for task rule information. In using this approach, our results replicate the fMRI findings of Etzel et al (2016) in human electroencephalographic data, showing that high reward prospect increased average task coding prior to target onset, and that the difference in task coding between reward conditions was associated with improvements in cognitive performance.…”
Section: Discussionsupporting
confidence: 86%
“…We explored this using RSA focused on the CON and FPN ROIs. We computed a consistency index associated with the maintenance of multivoxel representation of instructions from encoding to implementation stages (Qiao et al 2017; see We first collapsed across novel and practiced trials, and observed that the CON's consistency index was higher than the FPN's one (T 34 = 9.34, P < .001), suggesting more persistent task-set representations in the former network. We then explored variations within ROIs of both subnetworks, with two additional repeated-measures ANOVAs.…”
Section: Representational Similarity Analysismentioning
confidence: 99%
“…We explored this using RSA focused on the CON and FPN ROIs. We computed a consistency index associated with the maintenance of multivoxel representation of instructions from encoding to implementation stages (Qiao et al 2017;see Fig. 2), in which larger values indicated a higher consistency along time (see fMRI analysis section).…”
Section: Representational Similarity Analysismentioning
confidence: 99%
“…This finding informs current debates on the nature of task coding in the brain 27 . On the one hand, some have argued for flexible task coding especially in the fronto-parietal cortex 32,37 , often based on the multiple-demand network theory 31 . This account predicts that task coding should be stronger when task demands are high 32 , or when correct performance is rewarded 19 .…”
Section: Discussionmentioning
confidence: 99%